The 18 kDa Translocator Protein (TSPO) Overexpression in Hippocampal Dentate Gyrus Elicits Anxiolytic-Like Effects in a Mouse Model of Post-traumatic Stress Disorder - Zhang, Xiao-Ying; Wei, Wang; Zhang, You-Zhi; Fu, Qiang; Mi, Wei-Dong; Zhang, Li-Ming; Li, Yun-Feng (Frontiers in Pharmacology, 2018)
The translocator protein (18 kDa) (TSPO) recently attracted increasing attention in the pathogenesis of post-traumatic stress disorder (PTSD). This study is testing the hypothesis that the overexpression of TSPO in hippocampus dentate gyrus (DG) could alleviate the anxiogenic-like response in the mice model of PTSD induced by foot-shock. In this study, hippocampal DG overexpression of TSPO significantly reversed the increase of the contextual freezing response, the decrease of the percentage of both entries into and time spent in the open arms in elevated plus maze test and the decrease of the account of crossings from the dark to light compartments in light-dark transition test induced by electric foot-shocks procedure. It was further showed that the behavioral effects of TSPO overexpression were blocked by PK11195, a selective TSPO antagonist. In addition, the expression of TSPO and level of allopregnanolone (Allo) decreased in the mouse model of PTSD, which was blocked by overexpression of TSPO in hippocampal dentate gyrus. The difference of neurogenesis among groups was consistent with the changes of TSPO and Allo, as evidenced by bromodeoxyuridine (BrdU)- positive cells in the hippocampal dentate gyrus. These results firstly suggested that TSPO in hippocampal dentate gyrus could exert a great effect on the occurrence and recovery of PTSD in this animal model, and the anti-PTSD-like effect of hippocampal TSPO over-expression could be at least partially mediated by up-regulation of Allo and subsequent stimulation of the adult hippocampal neurogenesis.